PELATIHAN PERAKITAN KOMPUTER DAN INSTALLASI SISTEM OPERASI WINDOWS 7 - Budi Setiadi; Fathur Rahman; Dwi Retnosari (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
Computer Hardware and Software development today is so fast and felt very fosters learning various disciplines of science. The rapid development of the course must be accompanied by an attitude clicking up grade knowledge which is owned by all of us in terms of both hardware and software.Hardwre have expertise in the field of computers and software is the demands of the times like this, let alone Training Computer Assembling and installation of Windows 7 is one of the purposes or skills that must be held by a graduate school / vocational school or universities, especially the computer field. Computer assembly is how we can do the assembly and disassembly of computer hardware and also how to install the Windows 7 operating system.